Implementación de una máquina automática picadora de tallos de maíz - Almachi Paneluisa, Héctor Arturo (2016)
Nowadays, the “Cantón Mejía” is one of the main agricultural producers in the country, the corn is the most cultivated goods in this area, small local farmers are those who cultivate this product, a small part of this production is for human consumption, while the remainder is used as cattle feed, or is discarded because the small farmers don’t have the appropriate machinery to process the cornstalks due to the available machinery is too expensive and focus in industrial uses. By the current mentioned ahead problems was based on proposed design that will be implemented through the small farmers´ necessity to have a machine that helps them to process, sheathe and reduce the cornstalks costs production that is used as cattle feed.